Impact of Baizhu, Daqingye, and Hehuanhua extracts on the human gut microbiome - Lemons, Johanna M. S.; Narrowe, Adrienne B.; Liu, LinShu; Firrman, Jenni; Mahalak, Karley K.; Van den Abbeele, Pieter; Baudot, Aurélien; Deyaert, Stef; Li, Yanfang; Yu, Liangli (Lucy) (Frontiers in Cellular and Infection Microbiology, 2023)
In traditional Chinese medicine, the rhizome of Atractylodes macrocephala (Baizhu), the leaves of Isatis indigotica (Daqingye), and the flowers of Albizia julibrissin (Hehuanhua) have been used to treat gastrointestinal illnesses, epidemics, and mental health issues. Modern researchers are now exploring the underlying mechanisms responsible for their efficacy. Previous studies often focused on the impact of purified chemicals or mixed extracts from these plants on cells in tissue culture or in rodent models. As modulation of the human gut microbiome has been linked to host health status both within the gastrointestinal tract and in distant tissues, the effects of lipid-free ethanol extracts of Baizhu, Daqingye, and Hehuanhua on the human adult gut microbiome were assessed using Systemic Intestinal Fermentation Research (SIFR®) technology (n=6). Baizhu and Daqingye extracts similarly impacted microbial community structure and function, with the extent of effects being more pronounced for Baizhu. These effects included decreases in the Bacteroidetes phylum and increases in health-related Bifidobacterium spp. and short chain fatty acids which may contribute to Baizhu's efficacy against gastrointestinal ailments.The changes upon Hehuanhua treatment were larger and included increases in multiple bacterial species, including Agathobaculum butyriciproducens, Adlercreutzia equolifaciens, and Gordonibacter pamelaeae, known to produce secondary metabolites beneficial to mental health.In addition, many of the changes induced by Hehuanhua correlated with a rise in Enterobacteriaceae spp., which may make the tested dose of this herb contraindicated for some individuals. Overall, there is some evidence to suggest that the palliative effect of these herbs may be mediated, in part, by their impact on the gut microbiome, but more research is needed to elucidate the exact mechanisms.